(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The small, electronegative fluorine atom may have a huge influence on medicinal chemistry. Fluorine preferentially improves metabolic stability and membrane permeability in medicinal or diagnostic small molecule candidates. Many fluorinated medicine candidates have improved target protein binding affinity. Using a few carefully chosen examples from a wide range of therapeutic and diagnostic contexts, this brief introduction unifies these many fluorine applications in medicinal chemistry. Fluorine is often used in medicinal prospects, indicating a bright future in medication research and development. Installing fluorine rationally to optimize molecular properties will be a major issue.